Providing access to textual and image resources: analyzing tagging practices - Špiranec, Sonja (Array, 2014)
This study explores tagging approaches when different types of information sources are being tagged (textual resource vs. image). The research included a total of 80 students assigning tags on two sample resources - a scientific paper and a sample photograph. Differences between the two resources in tag assignment were analyzed with regard to tag number and distribution, both by using descriptive statistic and by introducing the Jaccard similarity coefficient – a metrics for comparing the tag sets created by each participant with the original keywords assigned by the author itself (scientific paper) or an expert indexer (image). The results showed differences that can be very important in designing tools for accessing and describing different information objects for various heritage institutions, such as museums with primarily visual objects, or libraries, housing primarily textual collections